Effect of spray drying temperature differences on the gross nutritional composition and solubility and sinkability of goat milk powder: Spray dried goat milk powder (Journal of the Bangladesh Agricultural University, 2019)
Spray drying is a method of drying powder via microencapsulated from liquid rapidly with hot temperature in order to increase the shelf life. Hence, the objectives of the study are to investigate the effect of spray drying temperature on the nutritional composition and physical properties of dry milk powder of Saanen goat milk reared in Sandakan using maltodextrin as binder. The experiment tested the inlet air temperature variation from 140°C - 220°C with triplicates. The result was analyzed by a one-way analysis variance (ANOVA) using the Statistical Analysis System (SAS) version 9.4. The results showed that there are significant (p